SINESTESIA DALAM KUMPULAN CERPEN PILIHAN RIAU POS 2012 DARI SEBERANG PERBATASAN - Rina, Sapta; Syafrial, Syafrial; Faizah AR, Hasnah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study was entitled “Sinestesia in the Selected Collection of Short Story of Riau Post 2012 dari Seberang Perbatasan”. The problems which was studied are; (1) How is the changes of Sinestesia patterns in the Collection of Short Story of Riau Post 2012 dari Seberang Perbatasan?, (2) What are the functions of sinestesia in the Selected Collection of Short Story of Riau Post 2012 dari Seberang Perbatasan?, and (3) What are the meanings of sinestesia in the Selected Collection of Short Story of Riau Post 2012 dari Seberang Perbatasan?. This study aimed to describe; (1) the changes of Sinestesia patterns in the Collection of Short Story of Riau Post 2012 dari Seberang Perbatasan, (2) the functions of sinestesia in the Selected Collection of Short Story of Riau Post 2012 dari Seberang Perbatasan, (3) the meanings of sinestesia in the Selected Collection of Short Story of Riau Post 2012 dari Seberang Perbatasan. The method of this study was descriptive. The data were collected through documentations and literature views. The findings found that the changes of sinestesia patternsin the Selected Collection of Short Story of Riau Post 2012 dari Seberang Perbatasan consist of; (1) from the sight sense to the hearing sense were 18 data, (2) from the smell sense to the sight sense were 3 data, (3) from the smell sense to the hearing sense were 1 data, (4) from the touch sense to the sight sense were 19 data, (5) from the touch sense to the hearing sense were 17 data, (6) from the taste sense to the sight sense were 18 data, from the taste sense to the hearing sense were 16 data. In term of functions; (1) creating certain images which produce the effects in clarifying the ideas to be presented were 78 data, (2) highlighting the images of some events were 11 data, and (3) the images of interesting events were 3 data. The uses of grammatical meanings were 92 data.Key Words: sinestesia, short story.